Can Rescheduling Explain the New Jersey Minimum Wage Studies? - Thomas R. Michl (Levy Economics Institute of Bard College, 1999)
This paper interprets the New Jersey minimum wage studies of Card and Krueger and their critics, Neumark and Wascher, through a scheduling model. The former found an increase in the number of workers in New Jersey fast-food restaurants after the state minimum wage was increased, while the latter found a decline in the total payroll hours of New Jersey restaurants. The scheduling model predicts that firms will substitute workers for hours per worker after a wage increase, which is consistent with both studies. Evidence from a subset of restaurants that reported both workers and hours data to Neumark and Wascher supports this interpretation. The New Jersey minimum wage appears to have redistributed income effectively to the targeted population by raising wages and reducing weekly hours per worker by just over one hour without causing any job loss.
Keywords: 330